The Relationship between Preschool Children's Numeracy Literacy Ability and Readiness for Primary School in Turen District - Aisyatun Nabilla; Eny Nur Aisyah; Rosyi Damayani Twinsari Maningtyas (Universitas PGRI Madiun, 2026)
Numeracy literacy is a crucial factor in shaping logical thinking skills; however, research quantitatively linking numeracy literacy to preschool children's school readiness—particularly within a local context—remains limited. These skills, which encompass number recognition, counting, and pattern comprehension, form the foundation for a child's readiness to enter primary school. This study aimed to determine the relationship between preschool children's numeracy literacy skills and their level of readiness for primary school. A quantitative approach with a cross-sectional correlational design was employed, involving 94 parents of children in